The direct and indirect effects of financial literacy and self-control on financial behavior - Purwatiningsih; Ujang Syaifudin Sumadi (PT Mattawang Mediatama Solution, 2025)
This study examines the role of simple lifestyle in mediating the effect of financial literacy and self-control on financial behavior. This survey design study involved 126 samples of undergraduate accounting students at Pamulang University. Using the Structural Equation Modeling (SEM) Partial Least Squares estimator method, this study found a positive effect of financial literacy on simple lifestyle. This study also found that financial literacy and self-control directly affect financial behavior. However, this study found no effect of a simple lifestyle on financial behavior. In addition, this study failed to prove the role of simple lifestyle in mediating the indirect effect of financial literacy and self-control on financial behavior. These results indicate that financial literacy and self-control are the most dominant factors in improving students' financial behavior. On that basis, higher education institutions should encourage the strengthening of financial literacy and self-control of students more intensively in order to improve their financial behavior. Good financial behavior in this context is a person's ability to organize, manage, and use their financial resources more wisely and rationally.